APSS: proactive secret sharing in asynchronous systems - Zhou, Lidong; Schneider, Fred B.; Renesse, Robbert Van (ACM Transactions on Information System Security, 2005)
APSS, a proactive secret sharing (PSS) protocol for asynchronous systems, is explained and proved correct. The protocol enables a set of secret shares to be periodically refreshed with a new, independent set, thereby thwarting mobile-adversary attacks. Protocols for asynchronous systems are inherently less vulnerable to denial-of-service attacks, which slow processor execution or delay message delivery. So APSS tolerates certain attacks that PSS protocols for synchronous systems cannot.